Comparison of Lamina Cribrosa Morphology in Eyes with Ocular Hypertension and Normal-Tension Glaucoma - Kim, Ji-Ah (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To characterize differences in the lamina cribrosa (LC) morphology between healthy, ocular hypertension (OHT), and naive normal-tension glaucoma (NTG) eyes. METHODS: Each group consisted of 80 eyes of 80 participants who were matched for age, sex, and axial length. The participants underwent enhanced-depth-imaging volume scanning of the optic nerve head using spectral-domain optical coherence tomography. The lamina cribrosa curvature index (LCCI) and lamina cribrosa thickness (LCT) were measured in horizontal B-scan images spaced equidistantly across the vertical diameter of the optic disc. RESULTS: The LCCIs in all seven planes were smaller in both OHT and healthy eyes than in NTG eyes (all P < 0.001), and did not differ significantly between the OHT and healthy eyes. The LCTs in all three planes were greatest in OHT eyes followed by healthy and then NTG eyes (all P < 0.001). Overall, the larger LCCI was associated with smaller LCT (P < 0.001). CONCLUSIONS: The LC was thin and steeply curved in NTG eyes than in healthy and OHT eyes. In OHT eyes, the LC was thick, and its curvature was comparable to healthy eyes. Longitudinal studies are required to examine whether the straight and thickened LCs in OHT eyes precede the onset of OHT or are a protective response to elevated intraocular pressure.